2016
DOI: 10.1177/1556264616651783
|View full text |Cite
|
Sign up to set email alerts
|

High School Youth’s Reactions to Participating in Mixed-Methodological Dating Violence Research

Abstract: The present study used a sample of high school youth (N = 218) and a mixed-methodological research design to examine high school students' reactions to participating in focus groups and completing surveys that inquired about dating violence (DV). Results showed that showed that 1.5% (n = 3) of the youth regretted participating in the study and 6% (n = 12) were upset by the study questions; being upset was attributed to personal experiences with DV and being disturbed by peers' responses during the focus group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 51 publications
1
43
1
Order By: Relevance
“…Although we did not measure depression in the current study, research suggests that Native American youth have higher rates of depression than White youth (Centers for Disease Control and Prevention, 2020). Higher rates of depression among this population may explain why a larger proportion of youth in the study reported being upset compared to youth in other studies (Centers for Disease Control and Prevention, 2020; Edwards et al, 2016; McClinton Appollis et al, 2015).…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…Although we did not measure depression in the current study, research suggests that Native American youth have higher rates of depression than White youth (Centers for Disease Control and Prevention, 2020). Higher rates of depression among this population may explain why a larger proportion of youth in the study reported being upset compared to youth in other studies (Centers for Disease Control and Prevention, 2020; Edwards et al, 2016; McClinton Appollis et al, 2015).…”
Section: Resultsmentioning
confidence: 51%
“…Modeled after previous research (Edwards et al, 2016), upset was assessed by asking: “Did anything we asked you about today make you feel upset.” The “yes” responses were coded as 1, the “no” responses were coded as zero, and the “I don’t want to answer” responses were coded as missing. If participants responded with a yes, that something made them feel upset, they were asked to answer an open-ended question inquiring about what made them upset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Banyard et al (2018) found that students’ perceptions of their level of influence on their campus are related to their engagement and bystander intervention. Edwards et al (2016) suggest inviting students to help create and deliver prevention messages. Many critiques of CPTED note that community members who are the most important stakeholders are often left out of community design and planning decisions.…”
Section: Dimensions Of the Built Environment On Campusmentioning
confidence: 99%